Strategies of state penetration: a network analysis of community governance in Shanghai - Tian, Felicia F.; Chen, Lin; Wang, Yihan (Frontiers in Political Science, 2024)
The Chinese state has been found to penetrate community participation to strengthen state infrastructure power, but understanding of these strategies remains equivocal. Using network analysis, we examine the strategies of state penetration on the relation between residents' committee (RC) and the thick network through routine community activities in an awardwinning gated community in Shanghai. The network is indeed horizontal (rather than hierarchical) around the RC. Instead of manifesting state power, popularity within the network translates to decision-making power in deciding routine community activities.However, residents with high network popularity are affiliated with the state, and this association may be generated by the state itself through a deliberate process of cultivation and co-optation. These findings shed light on the nuanced strategies of state penetration:Rather than overt suppression or infiltration, the state exerts authority over a horizontal network, which ensures that self-organized community participation occurs under state domination.